A novel single-step fabrication anode/electrolyte/cathode triple-layer hollow fiber micro-tubular SOFC. (27th September 2018) - Jamil, Siti Munira; Dzarfan Othman, Mohd Hafiz; Mohamed, Mohd Hilmi; Adam, Mohd Ridhwan; Rahman, Mukhlis A.; Jaafar, Juhana; Ismail, Ahmad Fauzi
Abstract: Micro-tubular solid oxide fuel cells (MT-SOFCs) have attracted much attention due to; higher volumetric output density, greater tolerance to cycling, quicker start-up capability and better mobility. Fabrication process of MT-SOFCs is one of the critical factor that ensures the success of a cell. There are three main components (i.e. anode, electrolyte and cathode) in the development of MT-SOFCs which are generally fabricated through separated and multiple laborious steps. This study aims to produce a novel anode/electrolyte/cathode (NiO-CGO/CGO/LSCF-CGO) triple-layer hollow fiber (TLHF) in a single-step using phase inversion based co-extrusion combined with co-sintering technique. The challenge lies within the diverse sintering behaviors among the anode, electrolyte and cathode layers at some point of the cell fabrication. In this study, the TLHF was found being able to survive the co-sintering at 1450 °C resulting a defect free precursor producing 0.48 Wcm −2 maximum power densities at 525 °C, which is comparable with the cell fabricated using conventional multiple-step process. Highlights: The first single-step production of complete MT-SOFC using phase inversion. Saving the production cost and time as it combines three processes into one. Decreasing the risk of inducing defect. Producing a great adhesion between layers. The maximum power density of 0.48 Wcm −2 was achieved at 525 °C.